Structure Properties of Koch Networks Based on Networks Dynamical Systems. (6th March 2017) - Zhai, Yinhu; Liu, Jia-Bao; Wang, Shaohui
Abstract : We introduce an informative labeling algorithm for the vertices of a family of Koch networks. Each label consists of two parts: the precise position and the time adding to Koch networks. The shortest path routing between any two vertices is determined only on the basis of their labels, and the routing is calculated only by few computations. The rigorous solutions of betweenness centrality for every node and edge are also derived by the help of their labels. Furthermore, the community structure in Koch networks is studied by the current and voltage characterizations of its resistor networks.